2012
DOI: 10.1117/12.914623
|View full text |Cite
|
Sign up to set email alerts
|

The need for speed

Abstract: Development of dielectric elastomer actuators has been mainly targeted towards achieving giant static strain with little attention paid to their response speed, which can, depending on materials used, be as long as tens of seconds. However, most of the practical applications require actuators capable of changing shape quickly, therefore a careful choice of materials and technologies for the dielectric and electrodes must be made. Test oscillating actuators, made with a range of silicone membranes with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Because of the design of the lens, the same membrane is used as dielectric for the actuator and as membrane encapsulating the liquid. In order to increase the device's tuning speed, we choose silicone membranes for the actuator, [11] and hence also for the lens. However, silicone elastomers are gas permeable, and swell when in contact with many non-polar liquids.…”
Section: Lens Design and Principlementioning
confidence: 99%
“…Because of the design of the lens, the same membrane is used as dielectric for the actuator and as membrane encapsulating the liquid. In order to increase the device's tuning speed, we choose silicone membranes for the actuator, [11] and hence also for the lens. However, silicone elastomers are gas permeable, and swell when in contact with many non-polar liquids.…”
Section: Lens Design and Principlementioning
confidence: 99%
“…Pelrine et al have reported, in 2000, a 117% uniaxial linear strain with an actuator patterned as a long strip on a uniaxially prestretch silicone elastomer. 1 More recently, Rosset et al have shown a 60% linear planar strain on a PDMS based DEA with rise time of less than 10 ms. 8 However, the existing theoretical guidelines for large actuation deformation of DEAs developed based on VHB films cannot be directly implemented to castable elastomers. 9,10 Unlike VHB, which is available as films with predefined thicknesses, PDMS or polyurethane are initially a resin and can be casted to form membranes of any desired thickness.…”
Section: Improved Electromechanical Behavior In Castable Dielectric Ementioning
confidence: 99%
“…the frequency at which the actuator can be charged and discharged). If it becomes smaller than the mechanical bandwidth, then the actuator becomes electrically-limited 29 .…”
Section: Discussionmentioning
confidence: 99%
“…As the data acquisition during the acquisition cycle is done in a quasi-static state, it is important to select a frequency for the cyclic actuation that is not too high, in order to ensure the same actuation stretch during the ageing phase and during the measurement phase. The mechanical bandwidth is dominated by the dielectric membrane material, although we have also previously shown that the electrodes have an impact on the response speed of DEAs 29 . We have characterised the stretch amplitude of an actuator made using a low-mechanical loss silicone (Dow Corning Sylgard 186.…”
Section: Actuation Frequencymentioning
confidence: 99%